A importância dos projetos sociais no contexto da escola de arte e cultura Pro-Arte Guamaré/RN - SOUZA, DANIELY (2024)
This article aims to highlight the importance of social dance projects to the academic and professional development of artists in the municipality of Guamaré/ RN, to present the opportunities that social projects provide to the communities of Guamaré/ RN and their students, as well as to demonstrate the benefits and results presented in the PROARTE social project. The methodology used to develop this work was based on the author's previous experiences and knowledge on the subject, in participatory action research, as well as through the application of interviews, text analysis and articles on the subject covered; observation and participation in the activities carried out in the program, experimentation and initial application to dance teaching. The importance of the chosen subject is justified by the need for opportunities for the artistic world in the city of Guamaré/RN, by the demand and social prejudice regarding artistic education as professional training, and how social projects are possible viable solutions to meet this demand and culturally produce more benefits for citizenship. It is concluded that social projects are a great cultural medium and provide distinct educational opportunities that increasingly promote the social and communicative formation of individuals, through the arts, as well as providing adolescents and young people with a more inclusive worldview.